Social capital and major depressive disorder among youth in Iran - Ebtesam Savari; Nastaran Nasirpour; Afarin Rahimi-Movaghar; Ahmad Hajebi; Vandad Sharifi; Masoumeh Amin-Esmaeili; Farid Najafi; Bahareh Fakhraei; Hamid Hakimi; Mehran Zarghami; Abbas Motevalian (BMC Psychiatry)
Abstract Background Social capital has long been recognized as a determinant of various health outcomes. However, the existence and magnitude of these associations may vary across different health conditions, different communities, and periods. This study aimed to investigate the association between social capital and major depressive disorder (MDD) among participants of the Persian Youth Cohort (PYC) study. Methods The PYC study enrolled 11,592 participants aged 15–34 years, from four cities in Iran representing a range of geographic areas. Baseline assessments included measuring lifetime MDD using the Persian version of the Composite International Diagnostic Interview (CIDI-2.1) and a 27-item social capital questionnaire to evaluate voluntary participation, trust, and sense of cohesion. We analyzed the baseline data using logistic regression to identify potential associations. Results The prevalence of lifetime MDD was 18.3%. The mean social capital-total score was 73.93 (SD = 13.93). A higher social capital-total score was inversely associated with the likelihood of MDD (AOR: 0.70, 95% CI: 0.66–0.74). Moreover, participants with higher scores in voluntary participation (AOR: 0.88, 95% CI: 0.83–0.92), trust (AOR: 0.65, 95% CI: 0.62–0.68), and sense of cohesion (AOR: 0.72, 95% CI: 0.68–0.75) were less probable to suffer from MDD. Conclusion Our study corroborates the existing evidence of the association between MDD and the three dimensions of social capital- participation, trust, and sense of cohesion- highlighting the consistency of these findings across diverse settings including young adults in Iran. The use of a valid diagnostic tool for assessing MDD adds robustness to our results, offering valuable insights for regions with similar social and cultural contexts. These findings suggest that interventions fostering social capital, particularly trust and cohesion, may help reduce the burden of MDD in youth.